Persepsi Mahasiswa Universitas Bung Karno Terkait Ketahanan Ideologi Nasional Menghadapi Ancaman Ideologi Kapitalisme Global - Salomon A.M. Babys; Edik Prayitno (FISIP Universitas Bung Karno, 2023)
Abstract The phenomenon of globalization which propagates the values of capitalism when compared with the values and philosophy of life of the Indonesian people which are grounded in Indonesian socialism (Pancasila) is a contradictory value, therefore it can be said that globalization has a propaganda purpose which is a serious threat to the existence of the ideological values of Pancasila. The author feels it is important in studying the